The Fundamental Right to Physical Liberty: Reflections from the Constitution, the Criminal Procedure Code and the Case Law of the Constitutional Court - Huerta Guerrero, Luis Alberto (2010)
The present paper analyzes the guarantees and minimum faculties related to the right to physical liberty in Peru, from the perspective of the Constitution, the Code of Criminal Procedure, the Constitutional Court and international treaties, such as the American Convention. on Human Rights, the International Covenant on Civil and Political Rights, among others. In this sense, in the first place, the prohibition of illegal detentions is developed. The Constitution establishes that the deprivation of physical freedom can only occur in cases of flagrante delicto and in the cases provided by law. Secondly, both international treaties, internal country rules, the Constitution and the Constitutional Court establish the prohibition of arbitrary detentions. In this sense, it is the duty of the justice operators to evaluate if the detention has been dictated according to laws and, in addition, if it respects the fundamental rights and the constitutional principles. As a third point, the author analyzes the right to immediate transfer before a judicial authority. The Constitution establishes that the maximum term of transfer of a detained person before a judicial authority is twenty-four hours or at the end of the distance. However, it is pointed out that in certain cases the maximum term is fifteen days. Fourth, the characteristics of judicial detention are developed. This type of measure must be provisional, motivated and exceptional, as indicated in international treaties. The Constitution does not establish any regulation regarding this measure; however, the Code of Criminal Procedure does. Fifth, the right to a reasonable time in cases of preventive judicial detention is analyzed. International treaties recognize this right and establish that if the period is not reasonable, the detained person has the right to recover their freedom immediately. On the other hand, although the Constitution does not recognize this right, the Constitutional Court recognizes it within the content of the right to physical liberty. Finally, the author develops the right of every person to the judicial protection of their fundamental rights, specifically, of their right to physical freedom. The doctrine states that the mechanism of protection of physical liberty is the process of habeas corpus. This is regulated in the Constitutional Procedural Code.